2020
DOI: 10.1177/0300060520979218
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the success of fallopian tube recanalization in treatment of tubal obstructive infertility

Abstract: Objective To examine potential risk factors associated with the success rate following fallopian tube recanalization (FTR) in infertile women with obstruction of the proximal fallopian tube. Methods We retrospectively studied patients who underwent FTR for tubal obstructive infertility between January 2016 and December 2018 at the Third Affiliated Hospital of Guangzhou Medical University. FTR was performed using a catheter and guidewire system to clear tubal obstruction. Predictive factors potentially associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…Some studies have shown that women with secondary infertility have a higher likelihood of having tubal occlusion, at least on hysterosalpingography, compared to those with primary infertility, with an adjusted risk ratio of 1.75 [19]. These findings are more often related to surgical causes than in woman with primary infertility, who, in contrast, show higher rates of congenital causes of tubal occlusion [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that women with secondary infertility have a higher likelihood of having tubal occlusion, at least on hysterosalpingography, compared to those with primary infertility, with an adjusted risk ratio of 1.75 [19]. These findings are more often related to surgical causes than in woman with primary infertility, who, in contrast, show higher rates of congenital causes of tubal occlusion [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Tubal obstruction is one of the most common causes of female infertility, accounting for approximately 14%–45% of all female infertilities ( Hanson et al, 2017 ; Shen et al, 2020 ). The recanalization rate of traditional tubal interventional procedures is approximately 90% ( Knuttinen et al, 2014 ; Ikechebelu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recanalization rate of traditional tubal interventional procedures is approximately 90% ( Knuttinen et al, 2014 ; Ikechebelu et al, 2018 ). But a high post-injection re-occlusion rate of 20–50% ( Knuttinen et al, 2014 ) has been seen, as well as a low pregnancy rate of about 30% ( Ikechebelu et al, 2018 ; Huang et al, 2019 ; Shen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations